The Eurasian Steppe is an important goat propagation route: A phylogeographic analysis using mitochondrial DNA and Y‐chromosome sequences of Kazakhstani goats. (26th December 2018) - Tabata, Risa; Kawaguchi, Fuki; Sasazaki, Shinji; Yamamoto, Yoshio; Bakhtin, Meirat; Kazymbet, Polat; Meldevekob, Alykhan; Suleimenov, Maratbek Z.; Nishibori, Masahide; Mannen, Hideyuki
Abstract: Goats ( Capra hircus ) were domesticated in the Fertile Crescent and propagated all over the world. The Silk Road through the Eurasian Steppe belt is a possible propagation route for domestic goats to Central Asia. Kazakhstan is in close geographical proximity to domestication centers and covers the majority of the Eurasian Steppe belt. In this study, we examined the genetic diversity and phylogeographic structure of Kazakhstani goats. The mtDNA sequences of 141 Kazakhstani goats were categorized into haplogroups A, C, and D, of which haplogroup A was predominant (97%), whereas haplogroups C and D were detected at low frequencies (1.4% each). The Kazakhstani haplotypes C were thzen categorized into Asian mtDNA type. Sequence analysis of the SRY gene on the Y‐chromosome in 67 male Kazakhstani goats revealed two haplotypes: Y1A (64%) and Y2A (36%). Analysis of the distribution of mtDNA haplogroups and SRY haplotypes from Eurasia and Africa demonstrated genetic similarity among animals from Kazakhstan, Mongolia, and Northwest China located on the Eurasian Steppe belt. These phylogeographic results suggested that the Eurasian Steppe belt was an important propagation route for goats to Central Asia.